"Multicolor" electrochemical labeling of DNA hybridization probes with osmium tetroxide complexes - Fojta, Miroslav; Kostecka, Pavel; Trefulka, Mojmír; Havran, Ludek; Palecek, Emil (Analytical chemistry, 2007)
Labeling of oligonucleotide reporter probes (RP) with electroactive markers has frequently been utilized in electrochemical detection of DNA hybridization. Osmium tetroxide complexes with tertiary amines (Os,L) bind covalently to pyrimidine (predominantly thymine) bases in DNA, forming stable, electrochemically active adducts. We propose a technique of electrochemical "multicolor" DNA coding based on RP labeling with Os,L markers involving different nitrogenous ligands (such as 2,2' -bipyridine, 1,10-phenanthroline derivatives or N,N,N',N'-tetramethylethylenediamine). At carbon electrodes the Os,L-labeled RPs produce specific signals, with the potentials of these differing depending on the ligand type. When using Os,L markers providing sufficiently large differences in their peak potentials, parallel analysis of multiple target DNA sequences can easily be performed via DNA hybridization at magnetic beads followed by voltammetric detection at carbon electrodes. Os,L labeling of oligonucleotide probes comprising a segment complementary to target DNA and an oligo(T) tail (to be modified with the osmium complex) does not require any organic chemistry facilities and can be achieved in any molecular biological laboratory. We also for the first time show that this technology can be used for labeling of oligonucleotide probes hybridizing with target DNAs that contain both purine and pyrimidine bases.
Keywords: Electrochemistry; Color; elektrody; DNA sondy; Nucleic Acid Hybridization; barva; elektrochemie; oxid osmičelý; hybridizace nukleových kyselin; Electrodes; DNA Probes; Osmium Tetroxide